Fiscal policy stabilization: Purchases or transfers? - Neil R. Mehrotra (Brown University, Department of Economics, 2014)
Both government purchases and transfers figure prominently in the use of fiscal policy for counteracting recessions. However, existing representative agent models including the neoclassical and New Keynesian benchmark rule out transfers by assumption. This paper provides a role for transfers by building a borrower-lender model with equilibrium credit spreads and monopolistic competition. The model demonstrates that a broad class of deficit-financed government expenditures can be expressed in terms of purchases and transfers. With exible prices and in the absence of wealth effects on labor supply, transfers and purchases have no effect on aggregate output and employment. Under sticky prices and no wealth effects, fiscal policy is redundant to monetary policy. Alternatively, in the presence of wealth effects, multipliers for both purchases and transfers will depend on the behavior of credit spreads, but purchases are preferred to transfers under reasonable calibrations due to its larger wealth effect on labor supply. When the zero lower bound is binding, both purchases and transfers are effective in counteracting a recession, but the size of the transfer multiplier relative to the purchases multiplier is increasing in the debt elasticity of the credit spread.
Keywords: E62; 330; fiscal policy; transfers; zero lower bound